Pt decorated CoFe2O4/Co3O4 nanosheets derived from 2D Fe–Co MOF for enhanced HCHO detection - Yuli Zhao; Mingyuan Wang; Siwei Liu; Xiangzhao Zhang; Guiwu Liu; Guanjun Qiao (Journal of Advanced Ceramics)
Highly sensitive and selective detection of volatile organic compounds (VOCs) is highly important, and designing a suitable microstructure and constructing heterostructures are two main effective strategies for gas-sensing materials to achieve this goal. In this study, Pt nanoparticle-decorated CoFe2O4/Co3O4 nanosheets were prepared via a solution method for highly accurate detection of formaldehyde (HCHO), where the CoFe2O4/Co3O4 nanosheets were derived from a two-dimensional Fe‒Co metal-organic framework (MOF). The response (Rg/Ra, where Rg represents the electrical resistance of the gas sensor when exposed to a specific target gas under defined conditions; Ra denotes the baseline resistance of the gas sensor in clean air) of the ternary Pt2/CoFe2O4/Co3O4 composite to 100 ppm HCHO at 280 °C can be calculated as 95.5, and it still exhibits a very high response to low concentrations of HCHO (1.26 to 50 ppb HCHO gas) and an ultralow limit of detection (LOD) of 6 ppb. The ternary composite also presented excellent reproducibility, selectivity, and long-term stability. The first-principles calculations demonstrated that the Pt/CoFe2O4/Co3O4 model presented the most stable structure and the strongest adsorption capacity for HCHO. The high sensitivity of Pt/CoFe2O4/Co3O4 to HCHO can be attributed mainly to the formation of multiple heterojunctions and the catalytic effect of the Pt nanoparticles. This work describes the facile preparation of MOF-derived multi-heterojunction materials and highlights the superior gas-sensing performance to that of VOCs.